Digital Transformation: A Threat to Meaningful Work? - Wike Been; Mark Huisman (Italian Labour Law e-Journal)
The latest industrial revolution, Industry 4.0, is characterised by digital transformation and like all previous industrial revolutions significantly impacting the content of jobs and the conditions under which they are performed. Some tasks have been fully automated, new ones have emerged and technological developments now allow for digital workplace surveillance and supervision, taking over tasks previously performed by managers. These changes in work are not neutral; they are likely to affect how useful workers perceive their jobs. Like during previous industrial revolutions, the impact can moreover be expected to vary between workers with low, intermediate and high educational levels. This study empirically explores these effects across European countries making use of the European Working Conditions Telephone Survey of 2021. The results of the hierarchical regression models show that although the overall impact on employees’ sense of having useful work may be positive, it is negative for highly educated workers. The centrality of computer work has a positive effect on the perception of having useful work for those with a low level of education and a negative effect for those with a high level of education. Moreover, experiencing extensive managerial authority of a digital system has a negative effect on the perception of doing useful work for workers across educational levels, but the negative effect is less pronounced for workers with a low level of education. This indicates that the digital transitions taking place in European workplaces are not neutral in terms of employees’ perceptions of their jobs. The overall effect can potentially be positive if employees are granted sufficient levels of autonomy in their jobs.